EPISTEMOLOGY OF ECOSYSTEM SERVICES IN THE FACE OF THE PROBABLE ENVIRONMENTAL OCCURRENCE OF ANTIBIOTICS AND DAMAGE BY HELMINTHS IN FISHES FROM LAKE TITICACA, PUNO-PERU - Argota-Pérez, George (2021)
The purpose of the study was to describe the epistemology of ecosystem services in the face of the probable environmental occurrence by antibiotics and damage by helminths in fish from Lake Titicaca, Puno, Peru. The need to understand, the practices and study approaches from the perspective of ecosystem services and how, the use of antibiotics impacts aquaculture sustainability and in particular, the farming of trout (Oncorhynchus mykiss Walbaum, 1972) is analyzed. Likewise, it is proposed to know, how it affects the concentrations of occurrence by antibiotics, the ecosystem service before the consumption of trout in breeding areas, if the tissues are deterministic to environmental tolerance and, the survival of the fish, presents some association between the immediate physiological, morphological and immunological effects, according to the occurrence by antibiotics, as well as, if there are biotransference values that generate a risk to human health due to the consumption of fish exposed to antibiotics and what would be the physical-chemical parameters of water quality that validate the bioconcentration and biacumulation in the tissue of O. mykiss in the presence of antibiotics. Similarly, if the design of production strategies and sustainable management of aquaculture is based on the knowledge of the potential risk of helminths and if antibiotics prevent diseases, but it is known if there are modified genes in helminths that cause diseases in fish. It is concluded, there is a need to validate scientific knowledge from the search for data chains in the face of interactive complexity that causes the environmental occurrence of antibiotics in the aquatic environment where the prevention of diseases in fish by parasitic helminths is allowed.